Biorefineries - Wagemann, Kurt.; Tippkötter, Nils.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book offers a comprehensive review on biomass resources, examples of biorefineries and corresponding products. The first part of this book covers topics such as different biorefinery resources from agriculture, wood processing residues and transport logistics of plant biomass. In the second part, expert contributors present biorefinery concepts of different biomass feedstocks, including vegetable-oils, sugarcane, starch, lignocellulose and microalgae. Readers will find here a summary of the syngas utilization and the bio-oil characterization and potential use as an alternative renewable fuel and source for chemical feedstocks. Particular attention is also given to the anaerobic digestion-based and Organosolv biorefineries. The last part of the book examines relevant products and components such as alcohols, hydrocarbons, bioplastics and lignin, and offers a sustainability evaluation of biorefineries.
From the Contents: Lignocellulose-Biorefinery: Organosolv-Processes -- Syngas-Biorefinery: Biomass-Gasification -- Syngas-Biorefinery: Syngas-Utilization -- Algal-Biorefinery -- Products: Lignin -- Biogas-Biorefinery: Syngas-Utilization -- Biomass Resources: Agriculture.
Keywords: Biotechnology; Chemistry, Technical; Renewable energy sources; Biotechnology; Industrial Chemistry; Renewable Energy